Promosi Coffee Tubruk Bamboo - Fajri Muhammad; San Ahdi (Institut Nalanda, 2023)
Coffee Tubruk Bamboo is a coffee brand in the city of Padang owned by Rizky Afrizal Candra. Coffee currently lacks a distinctive identity, therefore a new identity is created in the form of a logo. This logo incorporates colors and typography that encapsulate the original concept, aiming to make it memorable for both current and potential customers. The logo draws inspiration from the shape of a bamboo plant and coffee beans, symbolizing the signature of a business run from a bamboo-themed setting and complemented by the presence of coffee beans, all accompanied by a lettermark of the name “Coffee Tubruk Bamboo.